Effect of Total Hemoglobin level on HbA1c value in Type 2 Diabetes Mellitus patients (Bangladesh Journal of Medical Science, 2019)
Background & objectives: Glycated hemoglobin level (HbA1c) is widely used for the diagnosis, prognosis and monitoring of therapy in diabetes mellitus patients. The hemoglobin molecule is a part of the non- enzymatic glycation reaction, so it is assumed that the total hemoglobin concentration may have an effect on the HbA1c value along with blood glucose concentrations. Hence this study was done to evaluate the effect of total hemoglobin level on HbA1c value in type 2 diabetes mellitus patients and to find out whether reduced total hemoglobin level is reflected on the HbA1c level giving an erroneous impression on the glycaemic status of the patient.Methods: 100 diagnosed Type 2 Diabetes Mellitus patients were evaluated for their Fasting Blood Sugar (FBS), Total Hemoglobin level and HbA1c level and assessed for any effect of reduced total hemoglobin level on the HbA1c value.Results: It was observed that HbA1c value correlated significantly only with FBS level and total Hemoglobin level was not found to have any effect on the HbA1c value in Type 2 Diabetes Mellitus patients.Interpretation : The factor significantly affecting the HbA1c value is Fasting Blood Sugar level. Hemoglobin level doesn’t seem to be affecting the HbA1c indicating that Hemoglobin is not a significant predictor of HbA1c.Conclusions: This study documented a significant positive relationship between FBS and HbA1c level only. No correlation was found between total Hemoglobin level and HbA1c.Patients with mild to moderate anemia still revealed a high HbA1c value correlating only with the blood sugar status.Bangladesh Journal of Medical Science Vol.19(1) 2020 p.110-113